Color me in : a novel - Diaz, Natasha (Natasha E.) (Ember, 2020)
Fifteen-year-old Nevaeh Levitz is torn between two worlds, passing for white while living in Harlem, being called Jewish while attending her mother's Baptist church, and experiencing first love while watching her parents' marriage crumble.